Best proximity point theorems for $ α^{+} F, (θ-φ )$-proximal contraction - Rossafi, Mohamed; Kari, Abdelkarim (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, inspired by the idea of Suzuki type $ α^{+} F$-proximal contraction in metric spaces, we prove a new existence of best proximity point for Suzuki type $ α^{+} F$-proximal contraction and $ α^{+} (θ-φ )$-proximal contraction defined on a closed subset of a complete metric space. Our theorems extend, generalize, and improve many existing results.